STYLISTIC ANALYSIS OF THE POEM “DURING WIND AND RAIN” BY THOMAS HARDY - Aulia Putri (English Department, University of Riau Kepulauan, Batam,Indonesia, 2018)
This study is aimed to analyze Thomas Hardy’s poem “During Wind and Rain” from the view of stylistic analysis. It is seen through the aspects of graphological levels, phonological levels, morphological levels, and lexico-syntactical level. Graphological levels deal with punctuations. While, phonological levels discuss about rhyme, alliteration, consonance, assonance. Moreover, morphological levels are about affixes and compounding. At last, lexico-syntactical levels talk about semantic levels. This analysis is useful in revealing the meanings of the poem